Montenegro Financial Sector Assessment Program : Framework for Nonperforming Loans Workout and Insolvency and Creditor Rights - Jaeger, Johanna; Rouillon, Adolfo; Abrahams, Scott David (World Bank, Washington, DC, 2016)
This Technical Note (TN) examines the current state of NPLs in Montenegro, assesses the regulatory and supervisory framework as well as the insolvency and creditor rights regime, and makes recommendations for strengthening the framework. The analysis was carried out as part of the 2015 Financial Sector Assessment Program (FSAP), and was based on the legal and regulatory framework in place, the supervisory practices employed, and other conditions as they existed as of September 2015. The TN evaluates the legal, regulatory, and supervisory regimes in four key areas: (i) creditor rights and enforcement systems (for secured and unsecured credit); (ii) debt recovery and informal enterprise workout practices; (iii) formal insolvency system (liquidation and reorganization proceedings); and (iv) effectiveness of the relevant institutional, regulatory and supervisory frameworks in implementing laws, regulations, and supervisory requirements in this area. In addition, the TN assesses recent efforts at NPL resolution, including the implementation of a newly enacted law on voluntary out-of-court restructuring, and the role of special purpose vehicles.